A Warmer Arctic Compromises Winter Survival of Habitat-Forming Seaweeds - Gordillo, Francisco J. L.; Carmona, Raquel; Jiménez, Carlos (Frontiers in Marine Science, 2022)
Continuous winter darkness at a latitude of 79ºN was simulated in cultures of four species of Arctic seaweeds at 3 and 8ºC. The laminarians Saccharina latissima and Alaria esculenta, and the rhodophytes Phycodrys rubens and Ptilota gunneri were monitored for four months in total darkness and after one week following light return in early spring, under controlled laboratory conditions. Biomass loss during darkness was enhanced by the high temperature in all species. At 8ºC, the two laminarians were unable to resume growth upon re-illumination. Alaria esculenta showed new blade production by the end of the dark period, but only at 3ºC. In all species, the photosynthetic ability was sustained, not suspended, during the whole dark period. P. rubens exhibited lower photosynthetic potential at 8ºC than at 3ºC during the darkness period, but it was able to recover its O2 evolving potential upon re-illumination, as P. gunneri and S. latissima did, but the latter only at 3ºC. The reactivation of photosynthesis seemed to involve photosystem II over photosystem I, as 7 d of photoperiod after the prolonged darkness was not enough to fully recover the PAM-related photosynthetic parameters. Only small changes were recorded in the internal chemical composition (total C, total N, carbohydrates, proteins, and lipids), but species-specific differences were observed. Unlike subarctic areas with an operating photoperiod along the year, a warmer polar night might pose a limit to the ability of multi-year seaweeds to occupy the new ice-free illuminated areas of the Arctic coasts, so that newcomers will potentially be restricted to the spring-summer season.